The wild one - Petrie, Nicholas (Petrie, Nicholas. Peter Ash novel., 2020)
"War veteran Peter Ash tracks a murderer and his criminal family through the most forbidding and stark landscape he has ever encountered, in the latest thriller from the bestselling author of The Drifter"--